What Is Emerging? Supply Chains and the Remaking of Asia. Issue 2 (2nd April 2016) - Tsing, Anna
Abstract : A post–World War II Japanese business model has changed the cultural production of capitalism globally. Instead of a drive for uniformity, difference is a resource for the supply chains that have come to dominate Asia—and the world. This article offers a pocket history of the model's emergence and explores its implications for the (non)management of labor and natural resources. Heterogeneity and ruin intertwine in the making of supply chain pockets of political economy. Supply chains link precarity and prosperity, as well as varied cosmologies and ways of life, creating difference-in-connection. What we know as Asia reemerges within the linked niches and nodes of supply chains in which all kinds of difference matter and in which, indeed, global connection flourishes through structures for making and maintaining difference.